Respon pertumbuhan dan hasil tanaman jagung akibat perlakuan pupuk organik cair papua nutrient dan sistem budidaya - Baso Daeng; Rizald Hussein (Agrotek, 2021)
Corn are one of the leading food crop commodities. Corn, like plants in general, requires nutrients that are absorbed from the soil. One of the potentials of reliable organic fertilizers to support the Go Organic program is the utilization of liquid organic phosphate fertilizer "Papua Nutrient". This liquid organic fertilizer is product innovation of raw materials derived from West Papua's natural resources in the form of krandalit phosphate deposit soil. This study was conducted at the Amban Pantai Experiment Garden owned by the University of Papua, statistically designed using a completely randomized design. The combination of Papua Nutrient fertilizer and cultivated system resulted in total 10 treatments which were then repeated 4 times so that 40 experimental units were obtained. Observations were made on variable of growth and plant yield such as plant height, number of leaves, flowering time, length of panicles, and fresh weight of cobs. The combination of spraying treatment of liquid organic fertilizer Papua Nutrient with cultivation system performed a different influence on the growth and yield of corn crops. Corn crops that are treated with liquid organic fertilizer at a concentration of 10 cc/L of water in intercropping system performed the best results on the high parameters of the plant (4-6 weeks after planting) and the parameters of fresh weight of the cob.